ATRT-09. WHOLE GENOME AND EPIGENOME CHARACTERIZATION LINKS ATRT-MYC TO A SUBGROUP OF RENAL RHABDOID TUMORS. Issue 2 (22nd June 2018) - Johann, Pascal; Chun, Elizabeth; Erkek, Serap; Iskar, Murat; Perlman, Elizabeth; Hasselblatt, Martin; Pfister, Stefan M; Marra, Marco; Kool, Marcel
Abstract: Rhabdoid tumors (RTs) are pediatric cancers that account for nearly 10% of all tumors in infants. Currently, RTs are classified according to tumor location. In the central nervous system, they are called atypical teratoid/rhabdoid tumors (ATRTs) as compared to extra-cranial malignant RTs (MRTs). Regardless of the site of occurrence, RTs share histological characteristics and genetic alterations, with >95% of them showing loss of SMARCB1, a subunit of the chromatin-remodeling SWI/SNF complex. Molecularly, RTs are heterogeneous. Previous studies reported molecular subgroups within RTs of the same anatomic compartment. However, biological similarities among RT subgroups of different sites, and molecular characteristics shared among them remained unknown. To investigate the similarity of RTs from different anatomic sites at a molecular level, we compared DNA methylation, gene expression, and H3K27ac profiles of 150 MRTs and 161 ATRTs generated by WGBS, 450K/850K arrays, RNA-, and ChIP-Seq. Unsupervised clustering of DNA methylation data showed that a subset of MRTs clustered with the MYC-subgroup of ATRTs but not with SHH- and TYR-subgroups of ATRTs. Over-expression of MYC-ATRT representative genes, such as c-MYC and the non-coding regulatory RNA gene HOTAIR, was also observed in these MRTs. Furthermore, they were both characterized by global hypomethylation, high prevalence of partially methylated domains, and similar super-enhancer regions, identified by H3K27ac ChIP-seq analyses, such as those for the HOXC cluster genes. Our results indicate that MYC-ATRTs and a subset of MRTs share molecular similarities and associate with distinct developmental processes compared to other ATRT and MRT subgroups.